Optimal Control of a Single-Server Queue with Balking and Reneging - Blackburn, Joseph D. (Management Science, 1972)
We consider the problem of controlling a single-server queue by turning the server on and off. In addition to a Poisson arrival process and general service-time distribution, provisions for balking and reneging are included in the models, yielding a variety of applications. Stationary optimal policies which maximize expected discounted reward over an infinite horizon are shown to have a simple critical-number characterization. Algorithms for computing the critical numbers are described.